Psychological need satisfaction and autonomous motivation as predictors of readers’ continuous participation in reading promotion activities in university libraries - Wang Huijie,; Yu Haidong, (Malaysian Journal of Library and Information Science, 2025)
Readers are the target of university libraries' reading promotion activities, and their psychology is a key factor influencing their engagement. Studying the psychology of readers helps in the effective implementation of reading promotion activities. Based on self-determination theory, this article analyses the micro-mechanisms of readers' continuous participation in reading promotion activities from three perspectives: i) satisfaction of basic psychological needs, ii) autonomous motivation, and iii) intention to continue participation. A model was developed to determine the factors that influence readers' intention to continue participating in reading promotion programmes in university libraries. The model was validated using questionnaires and analysed using Structural Equation Modelling (SEM). The results showed that satisfaction of basic psychological needs positively influenced both intention to continue participation and autonomous motivation, with autonomous motivation mediating the relationship between satisfaction of basic psychological needs and intention to continue participation. This study is important to provide a theoretical frame of reference for related research and findings to improve the effectiveness of reading promotion activities in university libraries.